4(2x+4)+2(3x-5)=

Simple and best practice solution for 4(2x+4)+2(3x-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+4)+2(3x-5)= equation:


Simplifying
4(2x + 4) + 2(3x + -5) = 0

Reorder the terms:
4(4 + 2x) + 2(3x + -5) = 0
(4 * 4 + 2x * 4) + 2(3x + -5) = 0
(16 + 8x) + 2(3x + -5) = 0

Reorder the terms:
16 + 8x + 2(-5 + 3x) = 0
16 + 8x + (-5 * 2 + 3x * 2) = 0
16 + 8x + (-10 + 6x) = 0

Reorder the terms:
16 + -10 + 8x + 6x = 0

Combine like terms: 16 + -10 = 6
6 + 8x + 6x = 0

Combine like terms: 8x + 6x = 14x
6 + 14x = 0

Solving
6 + 14x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 14x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 14x = 0 + -6
14x = 0 + -6

Combine like terms: 0 + -6 = -6
14x = -6

Divide each side by '14'.
x = -0.4285714286

Simplifying
x = -0.4285714286

See similar equations:

| 9d-1d+2d-9=4d | | 2xy+5x=63 | | Z/10-5=6 | | 23-16.6=x | | x*x=16.6 | | -5+7x=7x+5 | | -5+12=47 | | 8(-2+x)-4x=32 | | 1/12-2/3m=1/3 | | 2a+7=4a-2 | | -4f+5=f+9f+5 | | x*x=14.6 | | 4(a+5)-2(a-5)= | | 12(x+3)=4(2x+9)+7x | | 5x/3-4=2x/5 | | 6g+2(4g-3)+10=32 | | 5=y+9 | | -30=-5/3(x=25) | | m/-4=5=14 | | -7r+6=-15 | | 5x-18=6x+8 | | f(x)=6x^3-53x^2-11x+2 | | .35y=15 | | 5x^2-lnx=0 | | -10-7m=-6m | | 3k+4=5k-10 | | 10+7p=24 | | 18x-8=13x-33 | | 2x-6+21=-3 | | -b-10=10+10+9b | | 4x-84=72-9x | | 4(2x+9)=-46+10 |

Equations solver categories